2017
DOI: 10.4311/2016lsc0119
|View full text |Cite
|
Sign up to set email alerts
|

The unity and diversity of the subterranean realm with respect to invertebrate body size

Abstract: A variety of subterranean habitats share an absence of light and a dependence on allochthonous productivity, but they differ in many features, including habitat volume. We examined the hypothesis that habitat volume is an important factor in community organization, especially with reference to body size, for a variety of communities for which data were available. We analyzed the results of ten studies that compared body sizes of obligate subterranean dwelling species with respect to habitat. All of the studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 27 publications
1
16
1
Order By: Relevance
“…Second, subterranean species are subjected to stratified environmental selection. The subterranean environment is generally compartmentalized into a series of nearly distinct microhabitats differing in light availability (Tierney et al, ), size of habitat pores (Pipan & Culver, ) and connectivity to the surface (Gers, ). A mosaic structure of subterranean microhabitats thereby provides a series of distinct experimental settings defined by distinct habitat‐filtering properties (Trontelj, Blejec, & Fišer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, subterranean species are subjected to stratified environmental selection. The subterranean environment is generally compartmentalized into a series of nearly distinct microhabitats differing in light availability (Tierney et al, ), size of habitat pores (Pipan & Culver, ) and connectivity to the surface (Gers, ). A mosaic structure of subterranean microhabitats thereby provides a series of distinct experimental settings defined by distinct habitat‐filtering properties (Trontelj, Blejec, & Fišer, ).…”
Section: Introductionmentioning
confidence: 99%
“…On a positive note, a number of studies have recently shown that SSHs actually represent promising model systems in ecology and evolution. SSHs are especially suitable models for understanding the role of habitat size as an evolutionary force constraining the size of organisms and conditioning their spatial niche Pipan 2015, Pipan andCulver 2017) and for investigating spatial and temporal dynamics of subterranean organisms (Crouau-Roy et al 1992, Gers 1998, Rendoš et al 2012, Ortuño et al 2013, Nitzu et al 2014, Jiménez-Valverde et al 2015, Brancelj et al 2016). Moreover, the investigation of these habitats is important for understanding the biogeography and the evolutionary patterns of the subterranean fauna (Christian 1987, Howarth 1993, Arnedo et al 2007, Ružička et al 2013.…”
Section: Shallow Subterranean Habitatsmentioning
confidence: 99%
“…Habitat availability and habitat (pore) size are the first factors limiting the occurrence of a subterranean species Culver 2001, Pipan andCulver 2017). Logically, a higher habitat and topographic heterogeneity should enhance a wider distribution in most subterranean taxonomic groups (Cornu et al 2013, Eme et al 2015, Christman et al 2016.…”
Section: Topographic Factors and Habitat Heterogeneitymentioning
confidence: 99%